Biomechanical evaluation of the tension band wiring principle. A comparison between two different techniques for transverse patella fracture fixation. Issue 8 (August 2017) - Zderic, Ivan; Stoffel, Karl; Sommer, Christoph; Höntzsch, Dankward; Gueorguiev, Boyko
Abstract: Purpose: The aim of this study was to investigate the validity of the dynamic compression principle of tension band wiring in two techniques for patella fracture treatment. Methods: Twelve human cadaveric knees with simulated transverse patella fractures were assigned to two groups for treatment with tension band wiring using either Kirschner (K-) wires or cannulated screws. Biomechanical testing was performed over three knee movement cycles between 90° flexion and 0° full extension. Pressure distribution in the fracture gap and fracture site displacement were evaluated at the 3 rd cycle in 15° steps, namely 90°–75°–60°–45°–30°–15°–0° extension phase and 0°–15°–30°–45°–60°–75°–90° flexion phase. Results: Mean anterior / posterior interfragmentary pressure in the groups with K-wires and cannulated screws ranged within 0.16–0.40 MPa / 0.12–0.35 MPa and 0.37–0.59 MPa / 0.10–0.30 MPa, respectively. These changes remained non-significant for both groups and loading phases (P ≥ 0.171). Mean anterior / posterior fracture site displacement for K-wires and cannulated screws ranged within −0.01–0.53 mm / 0.11–0.74 mm and 0.11–0.55 mm / –0.10–0.50 mm, respectively. Anterior displacement remained without significant changes for both groups and loading phases (P ≥ 0.112). However, posterior displacement underwent a significant increase in the course of knee extension for K-wires (P ≤ 0.047), but not for cannulated screws (P ≥ 0.202). Significantly smaller displacement at the posterior fracture site was detected in the group with cannulated screws compared to K-wires at 60° and 75° extension phase (P ≤ 0.017), as well as at 45°, 60° and 75° flexion phase (P ≤ 0.018). The critical value of 2 mm displacement at the posterior fracture site was not reached for any specimen and fixation technique. Knee extension was accompanied by synchronous increase in quadriceps pulling force. Conclusions: Tension band wiring fulfills from a biomechanical perspective the requirements for sufficient stability of transverse patella fracture fixation. It should, however, rather be considered as a static fixation principle than a dynamic one. Tension band wiring with cannulated screws was found advantageous over Kirschner wires in terms of interfragmentary movements at the posterior fracture site.